Conceptual modelling of microplastic fragmentation in the marine environment - Henri, Joshua Timothy (Stellenbosch : Stellenbosch University, 2025)
Henri, J. T. 2025. Conceptual modelling of microplastic fragmentation in the marine environment. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/22027e8e-3a00-45b1-b9f1-d68cc7a0abf2